2016
DOI: 10.1007/s10803-016-2874-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Executive Functioning and Symptoms of Attention-Deficit/Hyperactivity Disorder and Autism Spectrum Disorder in 6–8 Year Old Children

Abstract: This study examined relationships between executive functioning (EF) and ADHD/ASD symptoms in 339 6-8 year-old children to characterise EF profiles associated with ADHD and ADHD + ASD. ADHD status was assessed using screening surveys and diagnostic interviews. ASD symptoms were measured using the Social Communication Questionnaire, and children completed assessments of EF. We found the EF profile of children with ADHD + ASD did not differ from ADHD-alone and that lower-order cognitive skills contributed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Neely et al (2016) found a similar EF profile between ADHD+ASD and ADHD groups, while Pitzianti et al (2016) found similar EF profile between ADHD+ASD and ASD groups. Gomarus et al (2009) carried out a visual memory search task.…”
Section: Working Memorymentioning
confidence: 81%
See 4 more Smart Citations
“…Neely et al (2016) found a similar EF profile between ADHD+ASD and ADHD groups, while Pitzianti et al (2016) found similar EF profile between ADHD+ASD and ASD groups. Gomarus et al (2009) carried out a visual memory search task.…”
Section: Working Memorymentioning
confidence: 81%
“…Similarly, studies that had focused on response inhibition report that ADHD and ASD+ADHD patients show more dysfunction on inhibitory control compared to the ASD patients (Bühler et al, 2011;Sinzig et al, 2008b;Tye et al, 2014). In addition, even studies that do not find differences between the clinical groups on response inhibition suggest a tendency of decreased performance in the comorbid group (Neely et al, 2016;Pitzianti et al, 2016;Takeuchi et al, 2013). In contrast few studies show no differences between control group and clinical groups (Sinzig et al, 2008a, but see Sinzig et al (2008b); Van der Meer et al, 2012;Yerys et al, 2009), but results from BRIEF show a worse inhibition functioning in children with ASD and ASD+ADHD compared with TD children.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations